Incorporating Instagram Features in EFL Learning Environment - Disa Evawani Lestari; Emilius German (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
Instagram, famous for its easy picture and video sharing features, also has some other features, such as quiz, question, and poll, which can be used as English learning tools. The incorporation of Instagram becomes a valuable resource as most university students use Instagram. This study aims to explore those features and to investigate students’ perceptions of Instagram as learning tools. The research participants are 50 students who speak English as a foreign language (EFL) studying at a university which applies English as a medium of instruction (EMI). The participants follow the researcher’s Instagram account and are notified by email for every new post. They, therefore, can view and participate in those posts. The data is gathered from an online questionnaire. The results suggest that quiz is favored for its surprisingly effective function as a correction tool for common errors. In addition, cartoon post is favored as it provides funny and contextual use of the vocabulary which makes the vocabulary memorable. Hence, Instagram becomes effective English learning environment, which is supplementary to English classes, especially as an error correction and source of vocabulary input reaching massive number of students with only one post.